Business proposal: Codedsphere solutions development platform - Wang, Sebastian Guo Shu (2025)
This dissertation presents the business plan for Codedsphere, a Malaysia based custom software development company founded in 2024. Codedsphere aims to revolutionize the software development industry by creating a global platform that fosters a community of skilled developers who are treated as partners rather than employees. The company’s innovative model emphasizes transparency, fairness, and collaboration, positioning it to capitalize on the rapidly growing demand for customized software solutions.